Comprehensive Single Cell Analyses of the Nutritional Environment of Intracellular Salmonella enterica - Röder, Jennifer; Felgner, Pascal; Hensel, Michael (Frontiers in Cellular and Infection Microbiology, 2021)
The facultative intracellular pathogen Salmonella enterica Typhimurium (STM) resides in a specific membrane-bound compartment termed the Salmonella-containing vacuole (SCV). STM is able to obtain all nutrients required for rapid proliferation, although being separated from direct access to host cell metabolites. The formation of specific tubular membrane compartment, called Salmonella-induced filaments (SIFs) are known to provides bacterial nutrition by giving STM access to endocytosed material and enabling proliferation. Additionally, STM expresses a range of nutrient uptake system for growth in nutrient limited environments to overcome the nutrition depletion inside the host. By utilizing dual fluorescence reporters, we shed light on the nutritional environment of intracellular STM in various host cells and distinct intracellular niches. We showed that STM uses nutrients of the host cell and adapts uniquely to the different nutrient conditions. In addition, we provide further evidence for improved nutrient supply by SIF formation or presence in the cytosol of epithelial cells, and the correlation of nutrient supply to bacterial proliferation.